The hemoglobin, albumin, lymphocyte, and platelet score as a useful predictor for mortality in older patients with hip fracture - Zhicong Wang; Zhicong Wang; Hailong Liu; Mozhen Liu (Frontiers in Medicine)
ObjectiveWith a rapidly aging population, identifying effective prognostic predictors has always been a research hotspot in older patients with hip fracture. Recently, the score combining hemoglobin, albumin, lymphocyte and platelet (HALP) has been proposed as a novel biomarker for reflecting systemic inflammation and nutritional status. However, it is unclear whether the HALP score could be a potential prognostic indicator for mortality following hip fracture. Thus, the objective of this study was to explore the relationship between the HALP score and mortality risk in older patients with hip fracture, and further evaluate its predictive value.MethodsConsecutive patients were identified from our institutional hip fracture database over the period from January 1, 2013 to December 31, 2022. Outcomes were 90-day all-cause mortality and overall mortality at the longest follow-up. Multivariate Cox proportional hazard models and restricted cubic spline (RCS) models were employed to assess this relationship. The incremental predictive performance of the HALP score was assessed using the c statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI).ResultsIn total, 1707 patients were included with a median follow-up duration of 44.4 months, of whom 174 cases (10.2%) died within 90 days and 667 cases (39.1%) died at the longest follow-up. After multivariate adjustment, compared to tertile 1 group, tertile 2 and tertile 3 groups exhibited 0.676-fold (95% confidence interval [CI]: 0.471–0.972, p = 0.035) and 0.598-fold (95% CI: 0.390–0.918, p = 0.019) lower risks of 90-day mortality, as well as 0.681-fold (95% CI: 0.566–0.820, p < 0.001) and 0.618-fold (95% CI: 0.504–0.759, p < 0.001) decreased risks of overall mortality, respectively. For each unit increase in the HALP score, there was a significant decrease in 90-day mortality by 1.1% and in overall mortality by 1.0% (all p < 0.05). RCS analyses indicated nonlinear relationships between the HALP score and 90-day and overall mortality (all P for nonlinear <0.01). Moreover, adding the HALP score significantly improved the predictive ability for 90-day and overall mortality (all p < 0.05).ConclusionThe HALP score was independently associated with mortality risk, highlighting its potential as a useful prognostic indicator for predicting mortality in older patients with hip fracture.